Effect of spray drying parameters on the physicochemical properties and oxidative stability of oil from menhaden (Brevoortia spp.) and Asian swamp eel (Monopterus albus) oil extract microcapsules - Hashim, Nurmaryam Aini; Abdul Mudalip, Siti Kholijah; Mohd Arshad, Zatul Iffah; Mohd Azman, Nurul Aini; Mohd Norzi, Muhammad Fitri Azizi (Elsevier Ltd, 2023)
This work investigated the effect of spray drying parameters on the physicochemical properties and oxidative stability of oil from menhaden (Brevoortia spp.) and Asian swamp eel (Monopterus albus) oil microcapsules. Different emulsion formulations (Maltodextrin - MD, Maltodextrin+Gum Arabic - MD+GA, and Maltodextrin+Starch - M+S), inlet air temperatures (180, 190, and 200 °C), and feed flow rates (280, 382, and 485 mL/h) were applied to microencapsulate Brevoortia spp. oil. The best operating parameters were then used to microencapsulate the Monopterus albus oil. The moisture content, MC (%), peroxide value, PV (mEq/kg), free fatty acid, FFA (%), acid value, AV (mg KOH/g) and the morphology of the microcapsules were then evaluated. The Brevoortia spp. oil microcapsules produced with the Maltodextrin+Gum Arabic emulsion formulation, inlet air temperature of 200 °C, and feed flow rate of 280 mL/h showed the lowest moisture content, peroxide value, free fatty acid, and acid value of 9.145%, 3.293 mEq/kg, 4.891%, and 2.981 mg KOH/g, respectively. Using similar parameters, the microencapsulation of the Monopterus albus oil extract recorded a moisture content, peroxide value, free fatty acid, and acid value of 8.432%, 2.713 mEq/kg, 4.911%, and 2.871 mg KOH/g, respectively. In conclusion, improved physicochemical properties and oxidative stability of Monopterus albus oil extract microcapsules were achieved using the Maltodextrin+Gum Arabic emulsion formulation and spray drying at a high air inlet temperature of 200 °C and a low feed flow rate of 280 mL/h.